Sensory development of the child in Islam and its educational applications - شريف كوثر احسان كاظم (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The current research aims to establish and apply the sensory approach in the field of Islamic education, as well as to reveal the sensory stages that the child goes through from the embryonic stage to pre-school age (adult childhood) with the most prominent educational applications for sensory development. The researcher used the deductive approach by tracking texts that included senses. Man and his senses in the Islamic approach in the Holy Qur’an and the Sunnah of the Prophet, and the researcher reached several results, including: The Holy Qur’an and the Sunnah of the Prophet were the first to pay attention to the sensory development of the child and to talk about it and pay great attention to it until a letter was received regarding the rights of Imam Zayn al-Abidin (peace be upon him) in which the right was mentioned. Every human organ. Reading the Holy Qur’an during pregnancy has an impact on the child’s behavior after birth. There is a variety of applications of the sensory development approach in the field of its impact on the kindergarten child and evaluating his behavior and cognitive development.